Study ofthe flame resistance of low density polyethylene composites with oyster shells powder extracted from the Caspian Sea in Iran. - Mohammed, Ahmed J.; Radhi, Wisam A.; Ibrahim, Ibrahim K.; Mohammed, Faise J. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The flame resistance properties of oyster shells powder extracted from the Caspian sea in Iran composites were studied. (0%, 2.5%, 5%, 10%, 15% and 20%) (Wt. /wt) of added oyster shells powder with the particular size (≤ 250 μm) where composite with low density polyethylene and several factor were studied like average of average time of burning(ATB), rate of burning(RB), average extent of burning(AEB) and percentage of the time of burning(PTB). The obtained results showed that the average time of burning initiates strongly impacts with (5%), increasing weight preparation to(147Sec). And then begins to decline their behavior when increasing proportions weighted. While, the composite shows exception behavior at (20 %).
Keywords: Polymer composites lowdensity polyethylene oyster shells powder flame resistance Additives fire retardant